2009
DOI: 10.1111/j.1365-2788.2008.01148.x
|View full text |Cite
|
Sign up to set email alerts
|

Mental illness and intellectual disability in Magistrates Courts in New South Wales, Australia

Abstract: People with ID and/or CI were found to be over-represented in the Magistrates Court. Furthermore, results highlight the unmet mental health needs of this cohort in the criminal justice system. The results of the study have implications for the planning of services and diversionary options to facilitate better management of defendants with ID and/or CI with mental health needs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
32
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(36 citation statements)
references
References 22 publications
4
32
0
Order By: Relevance
“…As will be discussed further, the findings of Vanny et al (2009) and Mason and Murphy (2002) have implications for service delivery for people with complex issues around cognitive impairment when involved with the criminal justice system.…”
Section: Resultsmentioning
confidence: 93%
See 1 more Smart Citation
“…As will be discussed further, the findings of Vanny et al (2009) and Mason and Murphy (2002) have implications for service delivery for people with complex issues around cognitive impairment when involved with the criminal justice system.…”
Section: Resultsmentioning
confidence: 93%
“…Despite the over-representation of clients with cognitive disability within the criminal justice system, little is known about the prevalence of cognitive impairment among accused within the local courts system in NSW (Vanny, Levy, Greenberg, & Hayes, 2009). Further, little is known about the personal, health and mental health characteristics and their service provision needs in the community (Vanny et al, 2009, p. 289).…”
Section: Resultsmentioning
confidence: 98%
“…Several studies have demonstrated that people with ID are significantly over-represented at all levels of the criminal justice system, as defendants (Baldry, Dowse, & Clarence, 2011;Vanny, Levy, Greenberg, & Hayes, 2009) and as victims of crime; the latter are the focus of this article. Wilson and Brewer (1992) found that the crime rate for offences such as physical assault, sexual assault and robbery against persons with ID was nearly three times that of their non-disabled counterparts.…”
Section: Id Within the Criminal Justice Systemmentioning
confidence: 99%
“…Regarding interractions between police and people with an González 4 ID, whether victims or perpetrators, it is agreed that there isn't sufficient training (Bailey, Barr, & Bunting, 2001, Crown Prosecution Service, 2009Henshaw & Thomas, 2011). This is especially evident when obtaining their witness statements (Cedeborg & Lamb, 2008;Cedeborg, Danielsson, La Rooy & Lamb, 2009;Clare & Gudjonsson, 1995, Stacey, 1999, and the same could be said for the other actors in the criminal proceedings, including lawyers, judges, and prosecutors (Mercier & Crocker, 2010;Vanny, Levy, Greenberg & Hayes, 2009). Therefore, specific guidelines for this necessity are already being produced and distributed (Ministry of Justice, 2011) via the Police Intervention Guide for People with Intellectual Disability which has been developed in Spain (Alemany, Quintana, Recio, Silva, Manzanero, Martorell, & Gonzalez, 2012).…”
Section: Introductionmentioning
confidence: 99%